Relationship Between Mother Feeding Practices And Eating Behavior In Children Of 3-5 Years Old - Citra Windani Mambang Sari; Lusi Sri Solihah; Sari Fatimah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
The underweight and overweight of under-five children in Indonesia are considered as a serious problem by WHO. One of factor affecting is parents' urge in fulfilling their child's nutritional needs is often behind a less precise of feeding practice, this will have an impact on children's daily eating behaviour because children with 3 to 5 years old showed an attitude picky eater and included into active consumers. This study is intended to identify the relationship between mother's feeding behavior with 3 to 5 years old children’s eating behavior in Babakan Sari, Kiaracondong District. The study used a descriptive correlation method with the cross-sectional approach and proportional random sampling technique. The samples of the study were 89 people. The data were collected through the instrument Comprehensive Feeding Practice Questionnaire (CFPQ) for the practice of children feeding and Child Eating Behavior Questionnaire (CEBQ) for the children eating behavior. The data were analyzed through univariate and bivariate analysis used Chi-Square test. The results showed that 58,4% of the respondents conducted a less precise feeding practice and 78,7% of the mothers perceives eating behavior children have a good eating behavior. It can be concluded that is no relation between the practice of mother’s feeding behavior with the 3 to 5 years old children’s eating behavior in Babakan Sari, Kiaracondong District (p-value > 0,05).Keywords: eating behavior, feeding practice, nutrition, preschool, under-five children